Pengaruh Social Media Marketing, Ewom Dan Brand Experience Terhadap Keputusan Pembelian Skincare The Originote (Studi Kasus Pada Konsumen Lowokwaru, Kota Malang) - Afifah, Lailia; Asiyah, Siti; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The aim of this research is to test and analyze whether Social Media Marketing, Electronic word of mouth and Brand experience simultaneously influence the decision to purchase skincare that originates. The type of research used in this research is a survey with a quantitative approach. The population in this study is The Originote skincare consumers in Malang. Calculations show that the required sample size is 17 × 5, which is 85 respondents. The research uses multiple linear regression analysis using the SPSS 25 application. The research results show that there is a simultaneous influence between the variables Social Media Marketing (X1), E-WOM (X2) and Brand Experience (X3) on The Originote Skincare Purchase Decision (Case Study of Lowokwaru Consumers, Malang City). Keywords: Social Media Marketing, E-WOM, Brand Experience, and Purchase Decision